2006
DOI: 10.1073/pnas.0607117103
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of the lactic acid bacteria

Abstract: Lactic acid-producing bacteria are associated with various plant and animal niches and play a key role in the production of fermented foods and beverages. We report nine genome sequences representing the phylogenetic and functional diversity of these bacteria. The small genomes of lactic acid bacteria encode a broad repertoire of transporters for efficient carbon and nitrogen acquisition from the nutritionally rich environments they inhabit and reflect a limited range of biosynthetic capabilities that indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
1,039
2
13

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,232 publications
(1,111 citation statements)
references
References 60 publications
39
1,039
2
13
Order By: Relevance
“…In order to characterize the Lac 2 phenotype of L. casei ATCC 27139, the lacTEGF and galKETRM operons of L. casei ATCC 27139 were sequenced. Unlike those of L. casei 64H and ATCC 334 strains (Bettenbrock & Alpert, 1998;Makarova et al, 2006), the two operons were found to be linked together and organized as a lacTEGF-galKETRM gene cluster, as reported previously for Lactobacillus rhamnosus TCELL-1 (Tsai & Lin, 2006) and L. casei BL23 (GenBank accession no. FM177140).…”
Section: Introductionsupporting
confidence: 66%
“…In order to characterize the Lac 2 phenotype of L. casei ATCC 27139, the lacTEGF and galKETRM operons of L. casei ATCC 27139 were sequenced. Unlike those of L. casei 64H and ATCC 334 strains (Bettenbrock & Alpert, 1998;Makarova et al, 2006), the two operons were found to be linked together and organized as a lacTEGF-galKETRM gene cluster, as reported previously for Lactobacillus rhamnosus TCELL-1 (Tsai & Lin, 2006) and L. casei BL23 (GenBank accession no. FM177140).…”
Section: Introductionsupporting
confidence: 66%
“…Complete genome sequences of many lactic acid bacteria have been determined and these show a prominence of genes associated with the metabolism of simple carbohydrates, including oligosaccharides, and energy conversion systems (Makarova et al, 2006). L. reuteri 100-23 and L. johnsonii 100-33 persist in the gut of mice following a single inoculation and have an equal capacity to inhabit the forestomach of the animals.…”
Section: Discussionmentioning
confidence: 99%
“…lactis (Bolotin et al, 2001), SK11 L. lactis ssp. cremoris (Makarova et al, 2006) and KF147 L. lactis ssp. lactis (Siezen et al, 2010) were subjected to orthology prediction using the orthoMCL algorithm V2.0.2 (Li et al, 2003).…”
Section: Methodsmentioning
confidence: 99%